Neuroprotective potentials of honey for cerebral small vessel disease - Che Mohd Nassir, Che Mohd Nasril; Abdul Hamid, Hafizah; Hambali, Aqilah; Abd Manan, Nizar; Mehat, Muhammad Zulfadli; Ismail, Nurul Iman; Mustapha, Muzaimi (LIDSEN Publishing, 2022)
The nectar produced by bees in nature is known as honey and has been consumed for its nutritional and medicinal properties. There is growing evidence that honey and its compounds have anti-inflammatory, antioxidant and anti-microbial properties that are relevant to the maintenance of health and the prevention of illnesses, including cardiocerebrovascular disease. Cerebral small vessel disease (CSVD) is one of the major risk factors for diseases such as stroke, dementia, Alzheimer’s disease, and Parkinson’s disease. CSVD is prevalent with aging and the presence of vascular risk factors. Its most common deleterious effect on the brain parenchyma is a neurological problem, causing a spectrum of subtle clinical manifestations such as neurocognitive dysfunction, emotional or behavioral disturbances, and gait dysfunction. Moreover, the pathological mechanisms and preventive strategies for CSVD remain elusive, which is reflected in the continued lack of effective therapeutic and preventive therapies. Given the growing literature on honey and its compounds as a superfood-based preventive measure, this narrative review highlights the neuroprotective potentials of honey and its compounds in relation to the current understanding of CSVD pathomechanism.